2021
DOI: 10.1109/jphot.2021.3076895
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Underwater Wireless Optical Communications Links With Surface Currents and Tides for Oceanic Signal Transmission

Abstract: This report investigated underwater wireless optical communication (UWOC) links in the presence of surface currents and tides. The scenario of surface currents and tides was generated by a sea water tank, a water pipe, and a water pump of different flow rates. It built the oceanic channel of UWOC varied with the salinity and flow rate in the UWOC transmission. The data rate of UWOC links based on a 520-nm laser diode and none-return-to-zero on-off keying (NRZ-OOK) modulation can achieve 3.4 Gb/s at a bit error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The authors of [15] further investigated the effect of vehicle motion on a turbulence model by using experimental measurements at a 40 C temperature gradient. The UWOC system in [16] transmits information over a 1.8 m distance in a sea water tank at 3.4 Gbps. Orthogonal frequency division multiplexing over 10 m distance in shallow water is demonstrated in [17].…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [15] further investigated the effect of vehicle motion on a turbulence model by using experimental measurements at a 40 C temperature gradient. The UWOC system in [16] transmits information over a 1.8 m distance in a sea water tank at 3.4 Gbps. Orthogonal frequency division multiplexing over 10 m distance in shallow water is demonstrated in [17].…”
Section: Related Workmentioning
confidence: 99%
“…The authors measured BER, power, and loss rate as a function of (tap) water-wave level. In [17], the authors showed how salinity and flow rate of sea water induced turbulence in UWOC links, and they used a 520-nm laser. In [18], the authors investigated the effect of (tap) water-waves heights on the received optical power.…”
Section: A Related Workmentioning
confidence: 99%
“…The perpendicular rulers shown positioned in Figs. 1b and 1c allow to evaluate the amplitudes of the sinus and pulse waveforms, similarly to [16], [17] as discussed below. Fig.…”
Section: Experimental Setupsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] UWOC has many applications in military, civilian, and commercial, such as submarines, underwater unmanned vehicles, and deep-sea resource exploration. [5][6][7][8] In 1992, Allen et al exhibited that a vortex beam can carry orbital angular momentum (OAM). [9] The wavefront of the OAM beam has a helical phase and its electric field complex amplitude contains a term of exp [iℓθ ], where ℓ can be an arbitrary integer named topological charge or azimuthal index, representing the number of 2π phase shifts across the beam, and θ is the azimuthal angle.…”
Section: Introductionmentioning
confidence: 99%